New standards in training specialists in advertising and public relations in the context process - Shyian, V. (Continuing Professional Education: Theory and Practice, 2019)
Ukraine’s accession to the Bologna process resulted in improving the quality of Graduate degree. There are new features of pedagogical preparation of students. Preparation of highly skilled professionals is one of the most important issues of our time. We consider the known methods of teaching and searching for new methods and approaches to prepare studentsParticular attention should be paid for speciality, teaching experience in which in our country is negligible. One of them - specialty “Advertising and public relations.” In considering the training and education of students by the above qualification, should pay special attention to the demands of professional and personal character. The article deals with the new standards of prepearing of the advertising and public relations professionals in the system of Bologna; due attention paid to the specialty “Advertising and public relations” experience of teaching in which our country is negligible; investigated the features of educational process in the system of Bologna; contains a list of the necessary skills and knowledge acquired in the system of university training for future specialists in advertising and public relations. During the conducted analytical work revealed new standards in training in advertising and public relations in the system of the Bologna process, compared the features of the national education system in advertising and PR, found a number of requirements of professional and personal character required for future specialists in advertising and public relations.